2007
DOI: 10.1177/1089253207306098
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Consideration for Descending Thoracic Aortic Aneurysm Repair

Abstract: Anesthesia for surgery of the aorta poses some of the most difficult challenges for anesthesiologists. Major hemodynamic and physiologic stresses and sophisticated techniques of extracorporeal support are superimposed on patients with complex medical disease states. In this review, etiologies, natural history, and surgical techniques of thoracic aortic aneurysm are presented. Anesthetic considerations are discussed in detail, including the management of distal perfusion using partial cardiopulmonary bypass. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 95 publications
2
25
0
Order By: Relevance
“…As demonstrated in our previous study, increased BSCB leakage closely associated with invasion of exogenous ligands inducing immune and inflammatory responses were found during the course of spinal cord I/R injury, as evaluated by extravasation of EB dye [8,9]. Similarly, in this study, the bimodal distribution of EB extravasations was clearly observed as two phases, one stage from 6 to 18 h after surgery which continued for several hours, and the later one began at 36 h and peaked at 48 h (Figure 1), paralleling the clinical manifestation of an early ischemic phase with great risks of delayed and exacerbated injury, such as paralysis, two days after surgery [4,5]. …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As demonstrated in our previous study, increased BSCB leakage closely associated with invasion of exogenous ligands inducing immune and inflammatory responses were found during the course of spinal cord I/R injury, as evaluated by extravasation of EB dye [8,9]. Similarly, in this study, the bimodal distribution of EB extravasations was clearly observed as two phases, one stage from 6 to 18 h after surgery which continued for several hours, and the later one began at 36 h and peaked at 48 h (Figure 1), paralleling the clinical manifestation of an early ischemic phase with great risks of delayed and exacerbated injury, such as paralysis, two days after surgery [4,5]. …”
Section: Discussionsupporting
confidence: 70%
“…Spinal cord I/R injury after thoracic aortic surgery is invariably associated with dysfunction of the BSCB and plays a fundamental role in the progression of several unpredictable and disastrous complications, such as spinal cord swelling and secondary nerve injury, which account for much of the morbidity and mortality of this condition [4,5]. Spinal cord edema is often long lasting and resistant to therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord ischemia/reperfusion (IR) injury is a well-recognized clinical problem resulting in motor and sensory dysfunction that is characterized as temporary or permanent ischemia of the spinal cord following reperfusion in a setting of shock or thoracoabdominal aorta surgery [1]. The blood brain barrier (BBB) is a well-known specialized structure that maintains brain tissue in an immune-privileged environment [1].…”
Section: Introductionmentioning
confidence: 99%
“…The blood brain barrier (BBB) is a well-known specialized structure that maintains brain tissue in an immune-privileged environment [1]. The spinal cord, as a part of the central nervous system (CNS), connects the brain and the peripheral nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…6 Lung isolation is also beneficial as it reduces contamination of the dependent lung from blood and/or secretions. 7 A DLT presents several advantages for achieving OLV in TAA repair. It is relatively reliable to place, allows easy suctioning of both lungs, is unlikely to migrate during surgery, and in the case of migration can be repositioned with the use of a fiber-optic bronchoscope.…”
Section: Intraoperative Managementmentioning
confidence: 99%